Efficient Communication in Organizations - Federico Vaccari (Fondazione Eni Enrico Mattei (FEEM), 2022)
Organizations design their communication structures to improve decision-making while limiting wasteful influence activities. An efficient communication protocol grants complete information payoffs to all organization members, thereby overcoming asymmetric information problems at no cost. This paper characterizes efficient protocols assuming that: (i) some agents within the organization have the knowledge required for optimal decision-making; (ii) both the organization and consulted agents incur losses proportional to the exerted influence activities; and (iii) informed agents can discuss their strategies before being consulted. Under these assumptions, "public advocacy" is the unique efficient communication protocol. This result provides a novel rationale for public advocacy.
Keywords: D23; D82; D83; 330; Information; Communication; Organizations; Efficiency; Costly Talk